Bird strike virtual testing for preliminary airframe design - Perdikoulis, Petros V.; Giannopoulos, Ioannis K.; Theotokoglou, Efstathios E. (Emerald, 2021)
Abstract Purpose – The purpose of this paper is to use numerical methods early in the airframe design process and access the structural performance of wing leading edge devices made of different materials and design details, under bird strike events. Design/methodology/approach – Explicit finite element analysis was used to numerically model bird strike events. Findings – Structural performance charts related to materials and general design details were drawn to explore the design space dictated by the current applicable airworthiness requirements. Practical implications – This paper makes use of the current capability in the numerical tools available for structural simulations and exposes the existing limitations in the terms of material modelling, material properties and fracture simulation using continuum damage mechanics. Such results will always be in the need of fine-tuning with experimental testing, yet the tools can shed some light very early in the design process in a relative inexpensive manner, especially for design details down selection like materials to use, structural thicknesses and even design arrangements. Originality/value – Bird strike simulations have been successfully used on aircraft design, mainly at the manufactured articles design validation, testing and certification. This paper presents a hypothetical early design case study of leading edge devices for appropriate material and skin thickness down selection
Keywords: Smoothed Particle Hydrodynamics; Explicit Finite Element Analysis; Aircraft Design; Fiber Metal Laminate; Bird Strike